Oral Maxillofacial Surgical residency and its impact on the academic and research productivity at different levels in Pakistan - Humayun Kaleem Siddiqui; Kanza Ghauri; Muhammad Farhan Raza Khan (Journal of the Pakistan Medical Association, 2022)
Oral and maxillofacial (OMF) surgery is a unique speciality. In many countries, OMFS is a dental speciality but the scope of its practice significantly overlaps with other specialities, including otolaryngology, head and neck surgery, plastic surgery, and orthopaedics. Thus, OMF surgery represents a true amalgamation of medical and dental specialities. There are different requirements of OMF residency training, which include a dental undergraduate training, medical training, or both. The training pathways for this speciality have evolved much in the last three decades and there is still no consensus over a single uniform path of becoming an OMF surgeon. An OMF surgeon deals with trauma, cysts, tumours and other pathologies of the maxilla, mandible, and zygomatic complex that need surgical correction. In addition to being a diverse speciality, —Continue